RE-OS DATING OF THE MOLYBDENITE FROM THE QIUSHUWAN CU-MO DEPOSIT IN THE EAST QINLING AND ITS GEOLOGICAL SIGNIFICANCE - Guo B.J.; Mao J.W.; Qiu J.J.; Zhu X.L.; Li H.M.; Ye H.S.; Li M.W.; Qu W.J. (My University, 2006)
The Qiushuwan Cu-Mo deposit is an important porphyry-skarn type Cu-Mo deposit in the East Qinling. Six samples of molybdenite for Re-Os isotopic dating are analyzed and the model ages obtained from 145.57 ± 1.80Ma to 147.98 ± 2.21Ma, averaging 146.42 ± 1.77Ma, and a good isochronic age of 147 ± 4Ma. It is indicated that the Qiushuwan Cu-Mo deposit was formed in the late Jurassic, at the same period with the main porphyry-skarn type Molybdenum deposits of the south margin of North China craton and the copper deposits of the Middle-Lower Reach of the Yangtze River in the north margin of Yangtze craton, and is the component part of the second-term large-scale mineralization in the East China in Mesozoic. The Re contents of the molybdenite are up to 151.8 × 10-6 on average, and much higher than that of the molybdenum deposits in the south margin of North China craton occurred in late Jurassic. According to the contents of Re in molybdenite of the deposit and the geologic features of the porphyry, we consider the ore-forming materials are mainly derived from the lower crust.
Keywords: CU-MO DEPOSIT; OS-RE ISOTOPIC DATING; QINLING OROGENY; QIUSHUWAN; Мезозой::Юрская; Mesozoic::Jurassic